Anti-Inflammatory Activity of Bee Venom in BV2 Microglial Cells: Mediation of MyD88-Dependent NF-κB Signaling Pathway. (3rd August 2016) - Im, Eun Ju; Kim, Su Jung; Hong, Seung Bok; Park, Jin-Kyu; Rhee, Man Hee
Abstract : Bee venom has long been used as a traditional folk medicine in Korea. It has been reportedly used for the treatment of arthritis, cancer, and inflammation. Although its anti-inflammatory activity in lipopolysaccharide- (LPS-) stimulated inflammatory cells has been reported, the exact mechanism of its anti-inflammatory action has not been fully elucidated. Therefore, the aim of this study was to investigate the anti-inflammatory mechanism of bee venom in BV2 microglial cells. We first investigated whether NO production in LPS-activated BV2 cells was inhibited by bee venom, and further iNOS mRNA and protein expressions were determined. The mRNA and protein levels of proinflammatory cytokines were examined using semiquantitative RT-PCR and immunoblotting, respectively. Moreover, modulation of the transcription factor NF- κ B by bee venom was also investigated using a luciferase assay. LPS-induced NO production in BV2 microglial cells was significantly inhibited in a concentration-dependent manner upon pretreatment with bee venom. Bee venom markedly reduced the mRNA expression of COX-2, TNF- α, IL-1 β, and IL-6 and suppressed LPS-induced activation of MyD88 and IRAK1 and phosphorylation of TAK1. Moreover, NF- κ B translocation by IKK α / β phosphorylation and subsequent I κ B- α degradation were also attenuated. Thus, collectively, these results indicate that bee venom exerts its anti-inflammatory activity via the IRAK1/TAK1/NF- κ B signaling pathway.